Structural Decomposition as the Method of Industry Priority Monitoring for Regional Development - R. Safiullin, Marat; R. Safiullin, Azat; Z. Mukhametova, Guzel (International Journal of Engineering and Technology, 2018)
The work is devoted to the study of economic activity types at the sectoral and regional levels in order to form the sectoral priorities of economic development as the strategic guidelines for sustainable economic growth and the investment attractiveness of the territories. The theoretical and the methodological basis of the study was the fundamental provisions and the concepts of economic theory, the scientific works of domestic and foreign scientists in the field of socio-economic development of the region and regional economic systems, investment activities, strategic territorial and sectoral planning, periodicals, regulatory documents of the federal and regional levels, the modern methods of competitiveness and investment attractiveness evaluation. The study was carried out on the basis of information from the Federal State Statistics Service (ROSSTAT), the Territorial Body of the Federal State Statistics Service for the Republic of Tatarstan (Tatarstanstat), as well as on the basis of analytical information from the Center for Advanced Economic Research of the Academy of Sciences of RT. The methodological approach is a multi-level study consisting of a structural and dynamic analysis of economic activity types, the assessment of localization level and a structural decomposition of key indicator dynamics. The presented methodology allowed to carry out a comprehensive monitoring and the diagnostics of economic activity types, to determine the competitive positions of the Republic of Tatarstan for each type of activity and identify industry priorities that ensure the region investment attractiveness increase.Â Â